The friendship doll - Larson, Kirby (New York : Delacorte Press, 2011)
Follows the adventures of Miss Kanagawa, a doll made to serve as an ambassadors from Japan to the United States, as she makes friends and learns about love during the twentieth century.
5.2
3-6
3-6
Keywords: Ambassadors -- Juvenile fiction; Conduct of life -- Juvenile fiction; Dolls -- Juvenile fiction; Ambassadors -- Fiction; Conduct of life -- Fiction; Dolls -- Fiction; Ambassadors -- Fiction; Conduct of life -- Fiction; Dolls -- Fiction; United States -- History -- 20th century -- Fiction; United States -- History -- Fiction; United States -- History -- Fiction